Urban Forest Reserve Passarinho Forest: environmental practices and management mode - Fonseca, Anderson José da Silva; Silva, Helena Paula de Barros (Sociedade & Natureza, 2018)
The Urban Forest Reserve - FURB Mata do Passarinho, is part of a new category of the group of sustainable use of protected areas of the State System of Conservation Units of the Pernambuco’ State - SEUC, which ensure the participation of local communities in the process of management and nature conservation was one of the main purposes of this re-categorization. The research aimed to verify through research in loco if the management mode of FURB Passarinho Forest is in accordance with the laws establishing the SEUC based on partnership between the managing agency and the interests of society. The methodology consisted of literature and interview analysis with the managers of Conservation Units (CU). The results indicated that the law states the commitment of the reservation to be a space for interaction society and nature, where environmental education activities are developed, however, an inefficient public management scenario where lack of investment in the public sector and the little contingent of people was found servers to act as managers, not only of the category in question but all other (CUs)state of Pernambuco.Conservation Uni